Nutrient Composition, Antioxidant Andantiproliferative Properties Of Clausena Excavata Andmurraya Koenigii. - Wan Mohamad Zain, Wan Nor I'zzah (2005)
The proximate composition of Clausena excavata and Murraya koenigii leaves, together with the vitamin and mineral contents were investigated. Studies on the antioxidant and antiproliferative properties of the plant extracts and essential oils were also carried out. The proximate analysis showed that C. excavata leaves contained higher moisture, ash and crude fibre contents compared to M. koenigzi. The contents of vitamins A, C and E in C. excavata were found to be 47.78 mg/100 g, 586.30 mg/100 g and 267.67 mg/100 g, while in M. koenigzi the results were 1406.32 mg/100 g, 374.38 mg/100 g and 18.52 mg/100 g respectively. It seems that Murraya koenigii contained higher zinc (0.09 mg/100 g sample), copper (0.1 mg/100 g sample), sodium (0.4 mg/100 g sample) and potassium (0.91 mg/100 g sample) compared to Clausena excavata that showed 0.01 mg zinc and copper per 100 g sample, sodium (0.37 mg/100 g sample) and potassium (0.73 mg/100 g sample). Iron (0.32 mg/100 g sample), magnesium (0.96 mg/100 g sample) and calcium (5.46 mg/100 g sample) were found to be higher in C. excavata than M. koenigii that possessed 0.14 mg iron per 100 g sample, 0.76 mg magnesium per 100 g sample and 5.28 mg calcium per 100 g sample. The essential oils were obtained by hydrodistillation using fresh leaves and analysed using GC-MS spectrometry. The leaf oil of C. excavata was mainly made up of safrole (89.85%) while the leaf oil of M. koenigii was mainly made up of p-farnesene (42.85%). Other components that were present in appreciable amounts in M. koenigii oil were naphthalene (12.17%), acaryophyllene (8.09%), caryophyllene (5.47%) and eudesmo1(4.34%). The methanol and water crude extracts together with the essential oils of C. excavata and M. koenigii leaves were investigated for their antioxidant capacities in two different assays, namely the 0-carotene bleaching method and 1,l-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity. The methanol extract of M. koenigii showed the most potent antioxidant activity in p-carotene bleaching assay, giving a percentage of 86.13 %, while C. excavata showed 76.60 % in the assay. On the other hand, M. koenigii methanol extract showed weak effect in scavenging DPPH radical with an EC5o value of 2.14 mg/ml, compared to the methanol extract of C. excavata which exhibited 0.89 mg/ml. The water extract of C. excavata showed higher antioxidant activity in both p-carotene bleaching method (76.02 %) and DPPH radical scavenging method (EC50 value = 2.53 mg/ml) as compared to M. koenigii water extract which possessed 62.26 % antioxidant activity in Pcarotene bleaching method and 4.32 mg/ml ECso value in DPPH radical scavenging assay. Antioxidant activity of M. koenigii oil (91.01 %) was higher than C. excavata oil (66.3 %). Nevertheless, both of the essential oils did not present well in DPPH radical scavenging assay. The total phenolic content in the methanolic and water extracts of C. excavata and M. koenigii leaves, which were determined according to the Folin-Ciocalteu method, were expressed as gallic acid equivalents (GAEs); whereas the total phenolics in the methanolic extracts of both plants were higher than the water extracts. The methanolic extract of C. excavata had the highest phenolic content (103.33 mg of GAEs/g of sample extract) while M. koenigii methanol extract showed 63.92 mg of GAEs/g of sample extract. The total phenolic content of M. koenigii water extract possessed 53.62 mg of GAEs/g of sample extract while C. excavata exhibited 53.46 mg of GAEs/g of sample extract respectively. HepG2 (hepatic cancer), MCF-7 (hormone-dependent breast cancer), MDAMB- 231 (non-hormone-dependent breast cancer), HeLa (cervical cancer) and CAOV3 (ovarian cancer) cell cultures were used to determine the antiproliferative activities of C. excavata and M. koenigii. The growth of viable cells was evaluated by using ~icroculture-tetrazolium-(MTTa)s say. Clausine-B, which was isolated from C. excavata was found to inhibit 50% of HeLa cancer cells' proliferation at 22.90 pg/rnl, followed by M. koenigzi methanol extract (25.00 pg/ml), M. koenigzi essential oil (31.10 pg/ml) and C. excavata methanol extract (34.51 pg/ml). The Clausena excavata methanol extract, water extract and essential oil were found to cause 50% cell death of MCF-7 cancer cell line at concentrations of 36.50, 95.00 and 59.00 pg/ml respectively. Meanwhile, clausine-B and essential oil from M. koenigii were found to cause 50% cell death at 52.90 and 46.01 pg/ml respectively. For HepG-2 liver cancer cell line, the highest mean total ICso value could be seen in M. koenigii methanol extract which possessed 23.90 pg/ml. It was followed by clausine-B which was found to cause 50% cell death at a concentration of 28.94 pg/ml. The essential oil from M. koenigii and C. excauata methanol extract exhibited 48.00 and 53.03 pg/ml. Clausine-B and M. koenigii methanol extract were observed to inhibit the proliferation of MDA-MB-231 cell line at the concentrations of 21.50 and 37.98 pg/ml respectively. Three samples were found to cause 50% cell death of CAOV3 which is the ovarian cancer cell line. The samples are clausine-B (I& = 27.00 pg/ml), M. koenigii methanol extract (IC5o = 27.90 pg/ml) and C. excauata methanol extract (Ic50 = 79.00 pg/ ml). The findings of this study showed that the methanol extracts especially M. koenigii methanol extract have the great potential in antioxidant and antiproliferative activities. Clausine-B, was found to be active against all the cancer cell lines tested.